Venture capital - from the view of agent theory - Trinh, Ta Doan; Tung, Nguyen Thanh; Giang, Dang Thu; Hai, Ta Doan; Hai, Ta Doan; Hai, Ta Doan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Venture capital is a modality of investment playing an important role in promoting the success of start-up businesses, especially for those which based on high technology and new technology in many countries in the world. This is also the issue of great concern of managers, policy researchers in our country. However, the actual practice of Vietnam pointed out that not many high technologies and new technologies based startup businesses had received investment of venture capital funds, in spite that our country possesses an increasingly crowded force of highly qualified personnel with many unique innovative ideas and great ambitions to contribute to society. In addition, venture capital funds in Vietnam were mainly by nature came from foreign investment and no legitimate ones established from domestic sources. National authorities effort to establish a state owned fund to directly involve in remedying defects of capital markets for high-tech, new-tech start-up businesses and creating a flow of capital with catalytic role to attract the participation of local and foreign investors in venture capital activities. There have been still controversial opinions against these efforts, because of concerns about the high risk of start-up investment. Based on the analysis of specific nature of venture capital and from the perspective of economic relations between fund owners (investors) and start-up businesses (direct users of the fund), this paper aims at providing a better insight into the economic nature of the fund owners - users relationship through the perspective of agent theory - a theory has widely been used in political science and economics to justify specific character of the behavior of investors. Thereby, it provides a new perspective helping managers, policy researchers with useful information in the process of policy decision making with a view to promoting venture capital in developing start-up businesses in the field of high tech, new technology in our country. Code: 15121501